Simulation of the GaAsN-based Schottky solar cell prototype. Issue 1 (31st December 2022) - Boumesjed, A.; Mazari, H.; Ameur, K.; Benseddik, N.; Kadid, S.; Benyahya, N.; Benamara, Z.
Abstract : Dilute nitride semiconductors, such as GaAs1– x N x alloys, have attracted considerable attention due to their unique physical properties and wide range of their possible application in optoelectronics. In this report, a comprehensive numerical simulation under solar illumination of AM1.5G with SCAPS software, is used to find the optimum geometrical and physical parameters that yield the best efficiency of an n-GaAsN-based Schottky solar cell. This optimisation task is a function of the nitrogen concentration, the metal work function, the doping and the thickness of the GaAsN layer. According to our results, the choice of metal that allows to have a high barrier height while controlling the doping and the thickness of the GaAsN active layer allows the development of high quality GaAs1- x N x based SJSCs. Efficiency greater than 27% is expected with a nitrogen concentration of x  = 0.004 for this new design of the n-GaAsN Schottky solar cell.